Prestasi Belajar Perbankan Ditinjau Dari PemanfaatanPerpustakaan Sekolah Dan Persepsi Siswa TentangKeterampilan Mengajar Guru Pada Siswa Kelas XiAkuntansi SMK Batik 1 Surakarta - Yusti, Destian Aldi, Drs. Sami'an., M.M (2017)
The purpose of this research are: (1) To the student banking choose achievement from the utilization of school libraries, (2) To the student banking choose achievement from students's perception of teacher's teaching skill, (3) To the student banking choose achievement from the utilization of school library and students's perception about teacher's teaching skill. The tipe of research used is quantitative. The design of this study only use a question or question as means of collecting the main data taken from the sample in particular population. The population in this study is72 students of class XI of smk batik 1 surakarta, the 61 students were taken for sampling based on proportional random sampling method. The data collection technique using questionnaires that have been tested for the validity and reliability. Data analysis techniques used are t test, f test, coefficient of determination, multiple linear regression analysis, effective donation and relative donations. The result research are: (1) The significant influence betweenthe student banking choose achievementon the utilization of school libraries reviewed based on t test obtained from the value of t arithmetic> t table is 5,781 >2,002 with probability significance value <0.05 is 0,000 and effective contribution (se) of 39,45%. (2) There is significant influence between the student banking choose achievement on students's perception of teacher's teaching skil based on t test obtained value of t arithmetic > t table is 3.141 >2,002 with probability significance < 0.05 is 0.003 and effective contribution (SE) is 13.15%. (3) There is a significant influence between the utilization of school libraries and students's perception of teacher's teaching skil on the student banking choose achievementbased on f test known f arithmetic <f table is 32,227 <3,156 with significance probability value <0,05 is 0,000 with coefficient of determination (R2) equal to 52,6% whereas the remaining 47,4% is influenced by other variables of this study.